2021
DOI: 10.1186/s12870-021-02875-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical mapping of repetitive oligonucleotides facilitates the establishment of a genome map-based karyotype to identify chromosomal variations in peanut

Abstract: Background Chromosomal variants play important roles in crop breeding and genetic research. The development of single-stranded oligonucleotide (oligo) probes simplifies the process of fluorescence in situ hybridization (FISH) and facilitates chromosomal identification in many species. Genome sequencing provides rich resources for the development of oligo probes. However, little progress has been made in peanut due to the lack of efficient chromosomal markers. Until now, the identification of ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…campanulatus [ 30 ], G. biloba and P. densiflora [ 52 ], H. rhamnoides [ 17 ], R. wichurana [ 53 ], Passiflora species [ 62 ], Cestrum species [ 56 ], and V. foetida [ 57 ]. However, 5S rDNA has also showed high diversity in other plants, including A. hypogaea [ 20 ], Fragaria L. species [ 63 ], Crocus sativus L., Crocus vernus (L.) Hill [ 64 , 65 ], and P. concolor [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…campanulatus [ 30 ], G. biloba and P. densiflora [ 52 ], H. rhamnoides [ 17 ], R. wichurana [ 53 ], Passiflora species [ 62 ], Cestrum species [ 56 ], and V. foetida [ 57 ]. However, 5S rDNA has also showed high diversity in other plants, including A. hypogaea [ 20 ], Fragaria L. species [ 63 ], Crocus sativus L., Crocus vernus (L.) Hill [ 64 , 65 ], and P. concolor [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These oligonucleotide sequences can then be readily produced and tagged with fluorescent markers for use as oligo-probes in FISH [ 18 ]. Species identification based on such oligo-probes has been reported in an increasing number of plant species, such as Avena L. species [ 19 ], Arachis hypogaea L. [ 20 ], Saccharum spontaneum L. [ 21 ], Citrus L. species [ 22 ], Citrus sinensis (L.) Osbeck × Poncirus trifoliata (L.) Raf., CC [ 23 ], Populus L. species [ 24 ], Strobus Opiz species [ 25 ], and Pinus L. species [ 26 ]. However, information regarding H. rhamnoides is limited.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the ratio was relatively stable at 0 along the whole chromosome ( Figure 2 A,B), indicating no large segment deletions (more than 1 Mb), duplications, or translocations in the mutants. In order to validate the WGS observations, we designed two cocktails, Multiplex #3 and Multiplex #4 [ 21 ]. Multiplex #3 included FAM-modified oligo TIF-439, oligo TIF-185-1, oligo TIF-134-3, and oligo TIF-165.…”
Section: Resultsmentioning
confidence: 99%
“…Oligos are being developed for easy application, which allows researchers to obtain results by fast oligo-FISH or ND-FISH in a short time. Oligos have been developed and successfully used for cereals [ 40 , 41 , 42 , 43 , 51 , 52 ] and other crops [ 53 , 54 , 55 ]. In this article, we report the development of oligo-labeled probes, based on CS-1 [ 56 ] and CS-237 [ 31 ] repeats for rapid oligo-FISH.…”
Section: Introductionmentioning
confidence: 99%